Reshaping physical education curricula through the outcome-based education philosophy - Zhao Haojun; Lim Seong Pek; Xin Zhuozhuo (International Journal of Evaluation and Research in Education (IJERE), 2024)
In the contemporary educational landscape, the outcome-based education (OBE) philosophy has emerged as a pivotal approach, emphasizing the achievement of specific outcomes in the learning process. This study delves into the intricate relationship between physical education assessment methodologies for university students under the OBE framework and their subsequent social adaptability. This study used a sample of 100 physical education elective students from Qilu Normal University. It employed experimental and questionnaire methods to measure the effects of OBEdriven physical education assessment. Preliminary findings suggest a positive correlation between holistic assessment techniques, which consider physical prowess and cognitive understanding, and enhanced social adaptability among students. This adaptability was measured in teamwork, conflict resolution, and interpersonal communication. The study underscores the potential of the OBE philosophy in reshaping physical education curricula, making it more aligned with the broader objective of holistic student development. Further research is recommended to explore the longterm impacts of such assessment methods on students’ post-university life and career trajectories.